Verticality and Horizontality Monitoring of Mahakam Bridge Piers Post-Barge Collision Using Geodetic and Structural Instrumentation - Efendi, Aco Wahyudi; Safitri, Novia; Yusuf, Muh; Luzan, Irwan Faisal; Zubran, Azan (Department of Architecture, Faculty of Engineering, 2025)
This study evaluates the vertical and horizontal stability of Piers 2 and 3 of the Mahakam Bridge in Samarinda, East Kalimantan, a vital infrastructure subjected to heavy daily traffic loads. Monitoring was conducted using high-precision geodetic instruments, including Total Station, Geodetic GPS, Digital Level, and Tiltmeter, to accurately detect structural displacements. Data were collected over a 96-hour period and analyzed spatially using AutoCAD and ArcGIS. Results show that Pier 2 experienced lateral deflection ranging from 0.024% to 0.048%, while Pier 3 exhibited a maximum vertical deviation of 0.010% and horizontal shift up to 0.055%—within acceptable safety limits. The displacement patterns were linear and showed no abrupt angular changes. These findings confirm that the structure remains stable and safe for continued use, though periodic monitoring is recommended, especially during peak loads or after extreme weather events. This research provides a robust foundation for long-term bridge maintenance and technical decision-making.Penelitian ini mengevaluasi kestabilan vertikal dan horizontal Pilar 2 dan Pilar 3 Jembatan Mahakam di Samarinda, Kalimantan Timur, yang merupakan infrastruktur vital dengan beban lalu lintas tinggi. Pemantauan dilakukan menggunakan perangkat geodetik presisi tinggi, termasuk Total Station, GPS Geodetik, Digital Level, dan Tiltmeter, untuk mendeteksi pergeseran struktural secara akurat. Data dikumpulkan selama periode 96 jam dan dianalisis menggunakan AutoCAD dan ArcGIS untuk mendapatkan representasi spasial pergerakan. Hasil menunjukkan bahwa Pilar 2 mengalami defleksi lateral antara 0,024%–0,048%, sedangkan Pilar 3 menunjukkan deviasi maksimum sebesar 0,010% secara vertikal dan hingga 0,055% secara horizontal—masih dalam batas toleransi aman. Pola pergeseran menunjukkan kecenderungan linier dan tidak ada perubahan sudut ekstrem. Temuan ini menegaskan bahwa struktur masih stabil dan aman digunakan, namun tetap diperlukan pemantauan berkala, terutama setelah beban puncak atau kondisi cuaca ekstrem. Penelitian ini memberikan dasar kuat bagi pengambilan keputusan teknis dalam pemeliharaan jembatan jangka panjang.